A policy review of The Art of Recovery - Survive: Stabilise: Strengthen. The Report of the Culture, Arts and Heritage Recovery Taskforce, Northern Ireland Executive. August 2021 - Wright, John (Irish Journal of Arts Management and Cultural Policy, 2022)
This is a review of The Art of Recovery - Survive: Stabilise: Strengthen. The Report of the Culture, Arts and Heritage Recovery Taskforce. It focuses on a report published by the Department for Communities (DfC) in the Northern Ireland Executive and the recently established Culture, Arts and Heritage Recovery Taskforce. This paper employs a narrative policy analysis methodology to trace the different and often competing stories which underpin the report.